Analisis Keterampilan Menulis (Mahāratul Kitābah) Pada Peserta Didik Tingkat Madrasah Tsanawiyah: Studi Kasus Atas Ketiadaan Mata Pelajaran Kaligrafi di MTsN Binjai - Muhammad Gamal (Jurnal Recoms, 2024)
Mahāratul kitābah has several approaches, one of which is the art of calligraphy where the mahāratul kitābah is one of the four mahārah that are essential in the study of Arabic language. Therefore, it is important for Arabic learners to learn and master this art of calligraphy. In fact, the majority of schools from elementary to upper secondary schools do not give special attention to calligraphy subjects so that it affects the student's writing form that does not comply with the rules in force. The method used in this research is library research in which data is obtained from the library to provide arguments. The result of this study is that the school must give its own time for these calligraphy subjects so that the students of Madrasah Tsanawiyah Negeri Binjai can write Arabic characters well and correctly that correspond to the rules of writing.